A comparison of the Health Star Rating system when used for restaurant fast foods and packaged foods. (1st October 2017) - Dunford, Elizabeth K.; Wu, Jason H.Y.; Wellard-Cole, Lyndal; Watson, Wendy; Crino, Michelle; Petersen, Kristina; Neal, Bruce
Abstract: Background: In June 2014, the Australian government agreed to the voluntary implementation of an interpretive 'Health Star Rating' (HSR) front-of-pack labelling system for packaged foods. The aim of the system is to make it easier for consumers to compare the healthiness of products based on number of stars. With many Australians consuming fast food there is a strong rationale for extending the HSR system to include fast food items. Objective: To examine the performance of the HSR system when applied to fast foods. Design: Nutrient content data for fast food menu items were collected from the websites of 13 large Australian fast-food chains. The HSR was calculated for each menu item. Statistics describing HSR values for fast foods were calculated and compared to results for comparable packaged foods. Results: Data for 1529 fast food products were compared to data for 3810 packaged food products across 16 of 17 fast food product categories. The mean HSR for the fast foods was 2.5 and ranged from 0.5 to 5.0 and corresponding values for the comparator packaged foods were 2.6 and 0.5 to 5.0. Visual inspection of the data showed broadly comparable distributions of HSR values across the fast food and the packaged food categories, although statistically significant differences were apparent for seven categories (all p < 0.04). In some cases these differences reflected the large sample size and the power to detect small variations across fast foods and packaged food, and in others it appeared to reflect primarily differences in the mix of product types within a category. Conclusions: These data support the idea that the HSR system could be extended to Australian fast foods. There are likely to be significant benefits to the community from the use of a single standardised signposting system for healthiness across all fresh, packaged and restaurant foods.